Gastroretentive drug delivery system of ranitidine hydrochloride: Formulation and in vitro evaluation - Dave, Brijesh S. (Springer-Verlag, 2004)
The purpose of this research was to prepare a gastroretentive drug delivery system of ranitidine hydrochloride. Guar gum, xanthan gum, and hydroxypropyl methylcellulose were evaluated for gel-forming properties. Sodium bicarbonate was incorporated as a gas-generating agent. The effects of citric acid and stearic acid on drug release profile and floating properties were investigated. The addition of stearic acid reduces the drug dissolution due to its hydrophobic nature. A 3(2) full factorial design was applied to systemically optimize the drug release profile. The amounts of citric acid anhydrous (X(1)) and stearic acid (X(2)) were selected as independent variables. The times required for 50% (t(50)) and 80% drug dissolution (t(80)), and the similarity factor f(2) were selected as dependent variables. The results of the full factorial design indicated that a low amount of citric acid and a high amount of stearic acid favors sustained release of ranitidine hydrochloride from a gastroretentive formulation. A theoretical dissolution profile was generated using pharmacokinetic parameters of ranitidine hydrochloride. The similarity factor f(2) was applied between the factorial design batches and the theoretical dissolution profile. No significant difference was observed between the desired release profile and batches F2, F3, F6, and F9. Batch F9 showed the highest f2 (f2=75) among all the batches, and this similarity is also reflected in t(50) (∼214 minutes) and t(80) (∼537 minutes) values. These studies indicate that the proper balance between a release rate enhancer and a release rate retardant can produce a drug dissolution profile similar to a theoretical dissolution profile.